2016
DOI: 10.1159/000444491
|View full text |Cite
|
Sign up to set email alerts
|

Thiobarbituric Acid-Reactive Substances: Markers of an Acute Episode and a Late Stage of Bipolar Disorder

Abstract: Background: Lowered antioxidant defense systems and increased oxidative stress are implicated in bipolar disorders (BD). Early and late stages of BD may present different biological features (including the level of oxidative stress) and may therefore require different treatment strategies. The aim of this study was to analyze serum levels of lipid peroxidation [measured as thiobarbituric acid-reactive substances (TBARS), a derivative of malondialdehyde] in BD patients at various stages and phases of the illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 32 publications
2
23
0
2
Order By: Relevance
“…MDA, in turn, may cause deleterious effects to proteins and DNA thereby exerting neurotoxic effects and promoting cell death . Increased MDA levels in depression and bipolar disorder are now well established and have been consolidated in meta‐analyses …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MDA, in turn, may cause deleterious effects to proteins and DNA thereby exerting neurotoxic effects and promoting cell death . Increased MDA levels in depression and bipolar disorder are now well established and have been consolidated in meta‐analyses …”
mentioning
confidence: 99%
“…1,2 MDA, in turn, may cause deleterious effects to proteins and DNA thereby exerting neurotoxic effects and promoting cell death. 3,4 Increased MDA levels in depression and bipolar disorder are now well established [5][6][7][8][9] and have been consolidated in meta-analyses. [10][11][12] MDA is an oxidative-specific epitope (OSE) that is expressed on the cell surface of oxidized low-density lipoprotein (LDL), apoptotic and dying cells, 13 and circulating microparticles (MP).…”
mentioning
confidence: 99%
“…Reduced antioxidant capacity leads to the accumulation of Reactive oxygen species (ROS), which, in turn, causes oxidative damage to macromolecules. Indeed, biomarkers indicating oxidative damage were reported in BD patients: higher levels of protein carbonylation and lipid peroxidation [26]. In addition to the permanent changes, several studies found a correlation between manic or depressive mood states and the levels of oxidative damage biomarkers in bipolar individuals [26].…”
Section: Depressive and Bipolar Disorder (Bd)mentioning
confidence: 99%
“…Indeed, biomarkers indicating oxidative damage were reported in BD patients: higher levels of protein carbonylation and lipid peroxidation [26]. In addition to the permanent changes, several studies found a correlation between manic or depressive mood states and the levels of oxidative damage biomarkers in bipolar individuals [26]. In addition, neurotrophic factors, mainly brain-derived neurotrophic factor (BDNF), are important for neuroplasticity, a process that is impaired in patients suffering from BD [27,28], and Wnt and GSK-3 signaling [29] participate in the etiology of the disease.…”
Section: Depressive and Bipolar Disorder (Bd)mentioning
confidence: 99%
“…The presented results are a part of the large clinical study named De-Me-Ter (“Depression – Mechanisms – Therapy”, task 3.2 - Identification of endogenous marker of depression and therapy effectiveness) (Siwek et al 2016a, b; Siwek et al 2015; Styczeń et al 2015). …”
Section: Introductionmentioning
confidence: 99%